FARM SCALE NITROGEN BALANCES FOR TERRACED PADDY FIELD SYSTEMS - SUKRISTIYONUBOWO, .; LIANG, GIJS DU (Jurnal Sumberdaya Lahan, 2010)
Nitrogen balance at farm scale is not only important to refine the site specific nitrogen fertiliser application rate, but also to estimate how much nitrogen fertiliser should be provided every planting season at district level. The nitrogen fertiliser stock for the district can be calculated by multiplying the total planting areas with nitrogen fertiliser rate per hectare. The aims were to evaluate the nitrogen balance of terraced paddy field systems under conventional farmer practices and improved technologies during the wet season 2003-04 and dry season 2004 and to predict how much nitrogen fertiliser should be provided in every planting season for wetland cultivation in the Semarang district. The nitrogen input-output assessments were carried out in terraced paddy fields for the conventional farmer practices (CFP), conventional farmer practices + rice straw (CFP+RS), improved technology (IT), and improved technology + rice straw (IT+RS) treatments. Balances were computed based on the differences between input and output. Nitrogen originating from fertiliser (IN-1), recycled rice straw (IN-2), irrigation (IN-3), and precipitation (IN-4) were grouped as input. Nitrogen removal by rice grains (OUT-1) and rice straw (OUT-2) was considered as output. The input-output analyses showed negative nitrogen balances for all the treatments, both in the wet season 2003-04 and the dry season 2004. The more nitrogen deficit was observed when the nitrogen volatilisation was considered. The nutrient inputs, particularly coming from inorganic fertilisers, were not sufficient to replace the nitrogen removed by rice grains and straw. The application of only 50 kg of urea/ha/season with and without returning rice straw was not enough to reach the optimal yield and should be left out. To balance the nitrogen deficit and to improve cultural practices in wetland rice farming especially terraced paddy field system, about 200 -250 kg urea/ha/season is recommended when the ammonia volatilisation is not considered, where as when the ammonia volatilisation is taken into account about 250-300 kg urea/ha should be added. When the rice yield of 5.73 t/ha is targeted as reached in the IT+RS treatment even higher and the planting areas in the Semarang district is about 24.833 ha for the wet season, the amount of urea should be provided will be about 4.97-6.21 million tons/season/district, meanwhile for the dry season when about 18,440 ha wetland rice is expected to be cultivated is about 4.61 to 5.53 million tons urea/season/district should be available.